THE USE OF DISCORD APPLICATION IN VIRTUAL ENGLISH LEARNING: AN INVESTIGATION ON STUDENTS’ PERCEPTIONS - Evi Isfiatul Jannah; Daning Hentasmaka (UNIVERSITAS MUHAMMADIYAH METRO (MUHAMMADIYAH UNIVERSITY OF METRO), 2021)
Discord application, a voice and text chat platform usually used for games, social, class, or business groups, started to be used as one of the alternative media in virtual learning. A deeper investigation was conducted to get more information about students’ perception of virtual learning by using Discord application. This study implemented a qualitative research design, especially a case study. The data were collected from tertiary education students who were experienced in virtual English learning by using Discord by distributing an online questionnaire and doing interviews. Based on the results of data analysis, it was found that 89.72% of the students positively perceived the use of Discord application in virtual English learning. Some advantages of virtual learning by using Discord application found in the study were elaborated.